Proposal focus on the lineament of translation and interpretation (2019)
Proposal focus on the lineament of translation and interpretation Gratitude Problem question Justification General purpose Specific objectives State of the art Conceptual framework Methodological approach Data collection methods and techniques Conclusions Bibliografía